Texts and traditions religion in Shakespeare, 1592-1604 - Groves, Beatrice 1978- (Oxford English monographs, 2007)
Explores Shakespeare's engagement with the religious culture of his time. Through readings of a number of plays - Romeo and Juliet, King John, 1 Henry IV, Henry V, and Measure for Measure, this work explains allusions to the Bible, the Church's liturgy, and to the mystery plays performed in England in Shakespeare's boyhood.